The relationship between mindfulness, anxiety and depression during the COVID-19 pandemic: A meta-analysis of correlational studies - Xu, Fuming; Zhu, Wanling; Chen, Qian; Tang, Youmei (Frontiers in Psychology, 2023)
Background The emergence of the COVID-19 pandemic has created an environment in which numerous determinants of poor mental health are intensified. Lockdown, re-lockdown, and media coverage of the spread of the virus, have the potential to contribute to increased levels of anxiety and depression. Mindfulness may act as a buffer against COVID-19-related depressive and anxiety disorders. Methods We conducted a systematic review and meta-analysis by searching PubMed, PsycINFO, Web of Science, and Google Scholar for any study published between January 2020 and March 2022. In this study, Comprehensive Meta-Analysis Version 3.3 software was applied to evaluate the effect size by random effect model. In addition, the heterogeneity analysis was evaluated using indicators Q and I2 indicators. Three methods were used to test for publication bias: funnel plot, Classic Fail-safe N, and Egger’s linear regression. According to the features of the included articles, subgroup analysis was utilized for the moderator analysis of this study. Results The analysis finally included 12 articles (16 samples, N = 10,940) and obtained 26 independent effect sizes. In accordance with the meta-analysis, in the random effect model, the correlation between mindfulness and anxiety was −0.330 (p < 0.001), and the correlation between mindfulness and depression was −0.353 (p < 0.001), which supported the effect of mindfulness on anxiety and depression. In the meta-analysis of the correlation between mindfulness and anxiety, study region had an essential moderating effect (p < 0.001). The Sample type did not produce a significant moderating effect (p = 0.190). The mode of action of mindfulness was a significant moderator (p = 0.038). In the meta-analysis of the linkage between mindfulness and depression, regional differences had a significant moderating effect (p < 0.001). The sample type had no discernible moderating impact (p = 0.213). The mode of action of mindfulness was a significant moderator (p = 0.003). Conclusion Our meta-analysis indicated that there was an essential correlation between public mindfulness and mental health. Our systematic review added evidence supporting the beneficial nature of mindfulness. A cascading development of beneficial traits that improve mental health may start with mindfulness.